Influence of weather factors on forming chemical composition of plum fruits - Сердюк, М. Є.; Гапріндашвілі, Н. А.; Гогунська, П. В. (Scientific Progress & Innovations, 2013)
The influence of sum of active temperature which was higher than 10°С, the rainfall`s amount and the hydrothermal coefficient (HTC) on forming of soluble solids, organic acids, sugar and ascorbic acid of plum fruits has been investigated. The results of the correlated analysis give the opportunity to confirm that it`s not the weather of all vegetative period gives the most essential influence on the formation of the rate of plum fruit chemical composition in conditions of the South Steppe of Ukraine, but the weather of the last month before the harvest gives that influence when the most active forming of its quality takes place.